Friendly enemies : soldier fraternization throughout the American Civil War - Thompson, Lauren K. (Studies in war, society, and the military., 2020)
"Friendly Enemies analyzes the relations and fraternization of American soldiers on opposing sides of the Civil War, a representation of the common soldiers' efforts to fight the war on their own terms"--